Coastal debris survey in a Remote Island of the Chilean Northern Patagonia. Issue 1 (15th December 2017) - Perez-Venegas, D.; Pavés, H.; Pulgar, J.; Ahrendt, C.; Seguel, M.; Galbán-Malagón, C.J.
Abstract: Global marine litter pollution is increasing dramatically, and oceanic islands are one of the most vulnerable ecosystems due to their high debris accumulation rate compared to continental sites. Remote areas, such as inhabited islands, represent a perfect study case to track marine debris sources, due to the assumed low rates of local production of debris. Guafo Island is one of the largest islands of the Chilean Northern Patagonia and is considered a remote zone. The accessible coast of Guafo Island was monitored during four austral summers revealing higher levels of marine debris accumulation than continental Chile. Plastic was the most abundant type of debris constituting 50% of the total litter monitored. Our results suggest that most of the plastic identified is likely to be related to local fisheries activities. Mitigation measures including collaboration among fishing communities and scientists could contribute to reduce the coastal debris pollution in remote areas. Highlights: Levels of marine coastal debris found in the ecosystem were among the highest reported for the Chilean Coast. Almost 50% of total marine coastal debris was plastic. A decreasing trend on marine debris levels is likely to be related to a decrease in the fisheries activities on the island.